Yi Hua zhuxi wei shoude dang zhongyang he quanguo gezu renmin xin lian xin - Qi Menghui,
'The Central Committee of the Party, with Chairman Hua at its head, unites with the people of all nationalities of the nation'. Printno. 8086.918.